Ответы и объяснения

Лучший Ответ!
2013-05-03T16:48:54+04:00

1-2(x+2y)=5x+12y

6(х-4у)=5(3х+4у)-13

6(x-4y)=5(3x+4y)-13 
6x-24y-(15x+20y)+13=0 
-9x-44y+13=0 

y=-(9x-13)/44

1-2(x+2y)=5x+12y
1-2(x+2*(-(9x-13)/44))=5x+12*(-(9x-13)/44)
1-13//11x-13//11-5x-12*(-(9x-13)/44)=0 

-2//11-68//11x-12*(-(9x/44-13/44))=0

-2//11-68//11x-12*(-(9//44x-13//44))=0

-2//11-68//11x-(-27//11x+39//11)=0

-2//11-41//11x-39//11=0

-41//11-41//11x=0

x=(-41//11)/(41//11)

x=-1

6(x-4y)=5(3x+4y)-13 
6((-1)-4y)=5(3*(-1)+4y)-13 

-6-24y-5*(-3+4y)+13=0

-6-24y+15-20y+13=0
9-44y+13=0

22-44y=0

y=-(-22)/44

y=22/44

y=0.5


Ответ: x=-1y=0.5.